Why did it not work? Reflections on regulating Airbnb and the complexity and agency of platform capitalism. - Smigiel, Christian (Copernicus Publications, 2020)
This article deals with one of the most controversial topics in urban studies related to mobile capital and mobile people. At first glance this seems to be contradictory since numbers of short-term rentals have decreased dramatically due to the coronavirus (SARS-CoV-2) pandemic. However, this paper is not about numbers and statistics. Instead it discusses structural issues regarding governance and power relations which remain important topics (especially) in times of crisis. It provides insights regarding the following issues: firstly, it deconstructs different “myths” that still surround short-term rentals and Airbnb and secondly, it delineates the structural power of Airbnb as a new urban institution. This helps us to understand some of the conflicts over Airbnb and the pitfalls with current forms of regulation on the one side as well as showing the complexity and agency of short-term rentals on the other.
Keywords: Mietdauer; Wohnungsmarkt; Wohnungsnot; Gentrifizierung; Mietpreisentwicklung; Marktregulierung; Stadtpolitik; Kommunale Wohnungspolitik; Corona-Krise; Kurzzeitmiete; Online-Platform; Buchungsportal